Domain Wall Bianchi Type Vi0 Universe In F (R, T) Gravity - Hatkar, S. P.; Tadas, D. P.; Katore, S. D.
We consider the Bianchi type-VI0 space time with domain walls in the framework of the modified f (R, T ) theory of gravitation. To solve the field equations, we assume that the shear scalar σ is proportional to the expansion scalar ϴ. We also consider the parametrization of the equation of the state parameter of barotropic fluid and discuss the effect on domain walls. It has been observed that the domain wall may behave like dark energy. Some physical parameters are also discussed in detail. Рассмотрено пространство-время типа Бьянки VI0 с доменными стенками в рамках модифицированной теории гравитации f (R, T ). Для решения уравнений поля предполагается, что скаляр сдвига σ пропорционален скаляру расширения ϴ. Рассматривается также параметризация уравнения состояния баротропной жидкости и обсуждается влияние на доменные стенки. Было замечено, что доменные стенки могут вести себя как темная энергия. Также подробно обсуждаются некоторые физические параметры.
Keywords: Gravitation